2012
DOI: 10.3928/01477447-20120919-53
|View full text |Cite
|
Sign up to set email alerts
|

Use of Simple Algorithms to Predict Screw Length Facilitates Navigation-controlled Medial Opening-wedge Osteotomy Using the TomoFix HTO System

Abstract: This study was performed to establish simple algorithms to predict proper screw lengths for the 4 proximal holes of TomoFix plates (Synthes GmbH; Solothurn, Switzerland) based on radiographic mediolateral (ML) and anteroposterior (AP) dimensions of the proximal tibia and to determine how well these algorithms function for navigation-controlled medial opening-wedge high tibial osteotomy (HTO) using TomoFix. Experimental HTO surgery was performed in proximal tibial models manufactured for 30 patients undergoing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Screws selected for holes A, B, C, and D by using the simple algorithms were inserted without the use of fluoroscopy (Fig. 1j) [21]. The algorithms consisted of eight sub-algorithms, which were based on the anteroposterior (AP) length or mediolateral (ML) width measured on the pre-operative radiographs, and two algorithms for each of the four screws ( Fig.…”
Section: Surgical Techniquesmentioning
confidence: 99%
See 1 more Smart Citation
“…Screws selected for holes A, B, C, and D by using the simple algorithms were inserted without the use of fluoroscopy (Fig. 1j) [21]. The algorithms consisted of eight sub-algorithms, which were based on the anteroposterior (AP) length or mediolateral (ML) width measured on the pre-operative radiographs, and two algorithms for each of the four screws ( Fig.…”
Section: Surgical Techniquesmentioning
confidence: 99%
“…The authors recently reported a novel method to estimate the length of the proximal screws of the plate, using a pre-operative plain radiograph, which has so far functioned well in our navigated medial opening wedge HTO series [21]. These simple algorithms helped us to predetermine the screw length, without the need for fluoroscopy, so we anecdotally experienced reduced fluoroscopy use and operative time.…”
Section: Introductionmentioning
confidence: 97%